2021
DOI: 10.1002/ijc.33532
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID‐19 pandemic on the short‐term survival of patients with cancer in Northern Portugal

Abstract: The COVID‐19 pandemic led to potential delays in diagnosis and treatment of cancer patients, which may negatively affect the prognosis of these patients. Our study aimed to quantify the impact of COVID‐19 on the short‐term survival of cancer patients by comparing a period of 4 months after the outbreak began (2 March 2020) with an equal period from 2019. All cancer cases of the esophagus, stomach, colon and rectum, pancreas, lung, skin‐melanoma, breast, cervix, and prostate, from the Portuguese Oncology Instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 26 publications
(48 reference statements)
1
31
0
1
Order By: Relevance
“…The decline in resected malignancies from lower gastrointestinal tract, female genital tract and breast after period 1 might not only reflect a lower number of cancer diagnoses. It might be that a choice for other (neoadjuvant) treatment modalities like radiotherapy and/or chemotherapy was made more frequently under the given circumstances, thus postponing surgery and putting less strain on intensive care facilities [ 2 , 21 – 23 ]. However, a catch-up in numbers is not seen.…”
Section: Discussionmentioning
confidence: 99%
“…The decline in resected malignancies from lower gastrointestinal tract, female genital tract and breast after period 1 might not only reflect a lower number of cancer diagnoses. It might be that a choice for other (neoadjuvant) treatment modalities like radiotherapy and/or chemotherapy was made more frequently under the given circumstances, thus postponing surgery and putting less strain on intensive care facilities [ 2 , 21 – 23 ]. However, a catch-up in numbers is not seen.…”
Section: Discussionmentioning
confidence: 99%
“…Lui et al [9] concluded that the time to surgery did not impact overall survival or disease-free survival, but a time to surgery over six weeks improved the pathological complete response. However, Moraiset al [10] reported a higher short-term mortality rate in the patient group with mostly gastrointestinal cancer cases.…”
Section: Discussionmentioning
confidence: 96%
“…With respect to mortality in cancer patients, 24 indicators were identified from 4 articles. Twenty of these indicators resulted from one Portuguese study [105], the other 3 indicators showed a stable postoperative death rate in patients with head and neck cancer (France) [102], and a stable in-hospital mortality rate for orthopedic tumors at the traumatology department (Germany) [123]. One Turkish study [100] documented increased mortality in occlusive colorectal cancers patients.…”
Section: Discussionmentioning
confidence: 99%